(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
A hydroponic experiment was conducted in a greenhouse during (April-May 2021) at Tishreen University using Nutrient Culture System. The study consisted of different (NO3-:NH4+) ratios (100:0, 75:25, 50:50, 25:75, 0:100). The experiment lasted for 24 days. Plant growth, pH levels, water absorption and its relation to nutrient acquisition (H2PO4-, K+, NH4+, NO3-) were measured twice a week based on nutrient depletion from the nutrient solution. Growth of tomato plants was similar at 100:0, 75:25 and 50:50 (NO3-:NH4+). A high toxicity effects were recorded at high ammonium concentration in the nutrient solution, especially in 100% ratios. Results showed that shoot dry weight decreased by 36-75.5% at 75% and 100% NH4, respectively. The root dry weight decreased by 70.3% at the 100% NH4 treatment. When Nitrate was the sole nitrogen source, there was an increase in the cumulative absorption of water, NO3-, P and K, and decreased with introducing NH4 to the nutrient solution. It seems that nitrate can regulate NH4 absorption when both are present in the nutrient solution. Different forms of nitrogen influenced pH changes (set to pH=6). The pH increased above 7 in 100:0 and 75:25 (NO3-:NH4+) treatments, while decreased to 4.5 in the 25:75 treatment, and to 3 in the 0:100 treatment. This was due to the effect of nitrogen form (NO3-:NH4+) on the cation/anion balance in plant uptakes. Nutrients uptake were better in nitrate treatment especially in 100% and 75% nitrate treatments. Water uptake was closely correlated to nutrients uptake, especially nitrate and potassium, which indicate that water uptake is the main driving force for nutrient absorption, which in turn enhances plant growth. Water consumption increased with the increase of nitrate concentrations, especially in the 100:0 and 75:25 (NO3-:NH4+) treatments. Plants grown in NH4 showed a significant decrease in water consumption regardless of NH4 concentration. Key words: Hydroponics, tomatoes, nitrogen nutrition, water and nutrient absorption, pH changes.